COMPARISONAL ANALYSIS OF MYSQL AND MONGODB RESPONSE TIME QUERY PERFORMANCE - Nandy Naufal; Siti Nurkhodijah; Gregian Bayu Anugrah; Arief Pratama; Muhammad Ihsan Rabbani; Firgi Ahmad Dilla; Tiara Nurhaliza Anggraeni; Ricky Firmansyah (Pusat Riset dan Inovasi Nasional, 2022)
Query is the ability to display and or request data that is used to access data in the database system by using certain commands. Where a data obtained from one or more tables in the database according to what the user needs. The data can also interact with other data or tables with the aim of making it easier for the user to use it. The query response time is one of the considerations for testing databases. This journal will discuss two types of databases, namely MySQL (SQL) and MongoDB (NoSQL). Due to the increasing demand for data, data processors are competing to provide the right database with the best performance for applications or data processing. Then this journal provides a comparison analysis of MySQL and MongoDB databases in response time performance. This study uses the Query Runtime comparison execution test method between these databases. By using basic commands or DML queries, namely CRUD (Create, Read, Update, Delete). Several stages will be carried out, namely the determination of the dataset, implementation and testing, and analysis of the test results. In this study, trials were conducted on the insert, select, update, and delete processes with the data being tested were 100, 1000, 10000. After experimenting with MongoDB (NoSQL) and MySQL(SQL) databases. The MongoDB database has a faster query response time in the insert and delete process, for the query response time update and delete the MySQL database has a faster response time. Then it can be obtained that in query response time, the MongoDB database is superior in the update and delete processes with a runtime difference of 0.005 seconds and 0.017 seconds. MySQL database is superior in insert and select process with a difference of 4.137 seconds and 0.006 seconds.